-3(x+2)+4x=14

Simple and best practice solution for -3(x+2)+4x=14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x+2)+4x=14 equation:


Simplifying
-3(x + 2) + 4x = 14

Reorder the terms:
-3(2 + x) + 4x = 14
(2 * -3 + x * -3) + 4x = 14
(-6 + -3x) + 4x = 14

Combine like terms: -3x + 4x = 1x
-6 + 1x = 14

Solving
-6 + 1x = 14

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 1x = 14 + 6

Combine like terms: -6 + 6 = 0
0 + 1x = 14 + 6
1x = 14 + 6

Combine like terms: 14 + 6 = 20
1x = 20

Divide each side by '1'.
x = 20

Simplifying
x = 20

See similar equations:

| W=0.6w-20 | | -2.4=1.5k | | -1(1-4w)=2(2w-1)+1 | | 7p+6(-1+2p)=4(6+6p) | | 2x+2/9=2x-7 | | -18/2 | | 7p+6+12p=24+24p | | (lnx)2+2lnx=0 | | 6x+3/4=6x-1/8 | | .02x+.01(6000-x)=92 | | 3(6x+1)-6=-3-x | | x/5+x/8=7/5 | | 7p-4=8p-3 | | [x+8]=1 | | 1.2x+2.9=1.9x+2.2 | | x^2+(sqrt(2)x)-2=0 | | -3n+21-5n=-15-8n | | (x+2)lnx=0 | | 2+2x=3(4x-3x) | | 12x-48=12x-4 | | -4(6y-7)-y=-3(y-2) | | 1/3x-4=y | | 3[6-(-9x-7)]=216x+186 | | x^3+7x^2-5x^2-5x-35= | | 16-8x=14-7x | | 4(n+5)=-n+2(n-2) | | 4-4x-3=x^2 | | 5(x-1)-2(2x+3)=5x-4 | | 9(3x-1)-5=20x | | 172=125-x | | 5t^2+2=7t | | (2/3x+x)+16=102 |

Equations solver categories